Drivers of Stunting Among 0-23 Months Old Filipino Children Included in the 2003 and 2011 National Nutrition Survey - Angeles-Agdeppa, Imelda; Gayya-Amita, Patricia Isabel; Capanzana, Mario V. (International Journal of Child Health and Nutrition, 2019)
This study aims to evaluate household and individual level drivers of stunting among Filipino children aged 0-23 months in the 2003 National Nutrition Survey (NNS) and identified which factors pushed these same children to or out of stunting in middle childhood (8-9 years old) in 2011 Updating National Nutrition Survey (UNNS). All children aged 0-23 months in 2003 NNS were tracked if they’re still in 2011 UNNS by matching identifiers: region, province, municipality/city, name, and birthdate. There are 290 children included in both surveys. Children were categorized as: stunted in 2003 but not in 2011 (catch-up); stunted in 2003 & 2011 (persistently stunted); stunted in 2011 but not in 2003 (stunted later). The prevalence of stunting increased from 17.2% in 2003 to 35.2% in 2011. About 22.1% became stunted later; persistently stunted (13.1%); catch-up (4.1%). The individual-level factors that contributed towards persistent stunting are older age onset of stunting, underweight, and a <2 years birth interval; while the household level factors are those with ≥ 5 dependents, and a higher number of under-fives in the family. Households usage of water-sealed toilets and availability of electricity decrease the odds of persistent stunting and stunting later. No significant factors were found on what moves a child out of stunting. Living in shanties (Huts) pushed a normal child to be stunted in 2011. This study reflects the strong influence of both individual and household factors on stunting. These results could be useful in crafting area and problem-specific interventions.